Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/modpathol.2010.117
|View full text |Cite
|
Sign up to set email alerts
|

Poorly differentiated carcinoma of the thyroid: validation of the Turin proposal and analysis of IMP3 expression

Abstract: The Turin Proposal algorithm defines poorly differentiated carcinoma on the basis of the presence of solid/ trabecular/insular growth pattern, absence of conventional nuclear features of papillary carcinoma, and the presence of at least one of the following features: convoluted nuclei, mitotic activity Z3/10 HPF, or tumor necrosis. IMP3 appears to have diagnostic and prognostic value in many solid tumors, including thyroid carcinomas. We examined a series of follicular-cell carcinomas with prominent solid patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
143
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(164 citation statements)
references
References 28 publications
(29 reference statements)
9
143
2
10
Order By: Relevance
“…They applied both immunohistochemistry and qRT PCR, and for both techniques, they concluded that the expression of IMP3 seems to be a bad prognostic sign for PDC (9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They applied both immunohistochemistry and qRT PCR, and for both techniques, they concluded that the expression of IMP3 seems to be a bad prognostic sign for PDC (9).…”
Section: Discussionmentioning
confidence: 99%
“…An immunohistochemical score (IHC-score) was obtained by adding two scores (the lowest IHC score was 0 and the highest IHC score was 6); a score higher than 2 was considered positive, whereas a score 2 or lower was considered negative (9).…”
Section: Immunohistochemical Technique and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, there are striking regional differences in PDTC incidence rates; Northern Italy has the highest rates (15 %) with much lower rates in the United States (1.8 %) and Japan (\1 %), suggesting a multifactorial causative interaction between genetics, environment, and diet [13]. A recent study has shown that insulin-like growth factor-I mRNA binding protein-3 (IMP3) expression in PDTC appears to be an adverse prognostic factor, in that in univariate analysis, the risk of death was higher for age C45, tumors C4 cm, and IMP3 positivity by immunohistochemistry [14]. IMP3 expression has been shown to have diagnostic and/or prognostic value in many malignant solid tumors, including thyroid [14].…”
Section: Dedifferentiationmentioning
confidence: 99%